PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS NASABAH KREDIT PADA PT BANK MANDIRI KANTOR CABANG PEMBANTU MANDIRI MITRA USAHA PALU PASANGKAYU - Dasri, Muh. (Katalogis, 2017)
This study aimed to determine the influence of service quality on the loyalty of credit customers at PT Mandiri Bank Mandiri Assistant Branch Office of Palu Mandiri Business Partner of Pasangkayu in North Mamuju Regency. The theory used in analyzing the problem in this research was the theory of Kotler and Keller, better known as SERVQUAL (Service Quality), which saw service quality from the indicators of Physical Evidence (Tangibles), Reliability, Responsiveness, Assurance, and Empathy. This study was included to a survey research (Quantitative), whose the data collection technique used questionnaires and the samples were 100 respondents. The results of this study from all the quality dimensions/indicators between expectation and reality was equal to 0.288. This showed that there was a difference between the service quality perceived by the customers and the service quality expected by the customers. The Path Analysis resulted in the coefficient value of 0.251 accepted at the significance level of 5% (p<0.05), so it was concluded that there was significant influence of service quality on customer loyalty, while the multiple regression analysis resulted in the tcount value of 4.156 accepted at the significance level of 5% (p<0.05), so it was concluded that the customer satisfaction had positive and significant influence on customer loyalty.